Reliability of Smartphone Pulse Oximetry in Subjects at Risk for Hypoxemia. - Modi, Aashna M.; Kiourkas, Renee D.; Jie Li; Scott, J. Brady (Respiratory Care, 2021)
BACKGROUND: Pulse oximeters are used to measure ... and pulse rate. These devices are either standalone machines or integrated into physiologic monitoring systems. Some smartphones now have pulse oximetry capabilities. Because it is possible that some patients might utilize this technology, we sought to assess the accuracy and usability of smartphone pulse oximeters. METHODS: This was a prospective, observational study that involved noninvasive measurements of ... and heart rate with 3 devices: Masimo Radical-7, Kenek Edge with the Apple iPhone 6S, and the Samsung S8 smartphone. Ambulatory adult patients visiting our institution's pulmonary function lab for a 6-min walk test were eligible to participate in the study. Pretest and posttest results for each subject were obtained simultaneously using all 3 devices. All results were analyzed with the Spearman rho correlation test, and Bland-Altman plots were used to assess the agreement of measures between the devices. RESULTS: Forty-seven subjects were enrolled in the study, with pulmonary hypertension (30%) and COPD (23%) being the 2 major diagnoses. The mean ± SD difference between the Masimo and Apple devices for pretest ... was 2.3 ± 2.4%, and the difference for posttest ... was 2.1 ± 3.9%. The mean difference between the Masimo and Samsung devices for pretest ... was 3.2 ± 2.8%, and the difference for posttest ... was 2.4 ± 3.5%. The number of subjects who were unable to obtain ... was higher with the Samsung device than with the Apple device in both pretest (14 of 47 vs 3 of 47) and posttest (17 of 47 vs 5 of 47). In contrast, the Masimo device was able to measure ... in all subjects. CONCLUSIONS: Smartphone pulse oximeters were unreliable compared to a hospital pulse oximeter. Further research is needed with evolving technology to better understand smartphone pulse oximetry. (ClinicalTrials.gov registration NCT03534271.)